Cellular renovation of cervix uteri under cervical intraepithelial neoplasia unit with human papilloma virus has to women with secondary infertility. - Kindrativ, E. O. (Морфологія / Morphologia / Morfologìâ, 2011)
In article expound results of immunehistochemical research ectocervix cellular renovation processes under cervical intraepithelial neoplasia with used of monoclonal antibodies Ki-67 & p63 (DakoCytomation). In research used a cervix uteri biopsy material from 56 women with secondary infertility. Preliminarily were identifying high oncogenous risk human papilloma viruses (HPV). For women with secondary infertility under cervical intraepithelial neoplasia (CIN) we observed activation of cellular proliferation processes. Index of proliferation activity about CIN-I is 9,3±4,2%, about CIN-II - 39,23±4,3%, about CIN-III - 64,9±4,5%. Cellular renovation processes going to increase correlation index of cellular proliferation and proapoptosis processes (Кі-67/р63). Thereby we establish that according with rapidity of cervix uteri dysplastic change occurred increase proliferate activity together activation processes of proapoptosis programs.